(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of hypertension and describe selected factors associated with hypertension among individuals aged 18–69 years in Hanoi in 2025. Methods: A cross-sectional descriptive study was conducted on 2,912 individuals aged 18–69 years. A two-stage random sampling method was applied from July to December 2025 in Hanoi, Vietnam. Result: The prevalence of hypertension was 32.24%. The mean systolic and diastolic blood pressures were 124.72 ± 18.7 mmHg and 78.47 ± 12.21 mmHg, respectively, with higher values observed in males than females. The proportion of participants with adequate knowledge of hypertension was low (6.5%). Most participants had 1–2 non-communicable disease risk factors (59.86%). Multivariable logistic regression analysis showed that age and sex were significantly associated with hypertension. Specifically, individuals aged 45–69 years had a significantly higher likelihood of having hypertension compared with those aged 18–44 years (OR = 8.3; p < 0.001). Men had a higher risk of hypertension than women (OR = 1.9; p < 0.001). In addition, a history of diabetes mellitus was identified as an independent factor associated with hypertension (OR = 2.5; p < 0.001). Overweight and obesity were also significantly associated with hypertension, increasing the likelihood of the condition (OR = 2.5; p < 0.001). No statistically significant associations were found between hypertension and knowledge of hypertension, dietary factors, alcohol consumption, or physical activity.